Evaluation of an unsymmetrical dialkylphosphinic acid INET-3 for cobalt and nickel extraction and separation from sulfate solutions. (1st September 2020) - Fu, Jiashuai; Xu, Wen; Yu, Fengshan; Wang, Huajun; Wang, Junlian
Highlights: INET-3 was first introduced to Co/Ni separation. It possesses stronger extractability than Cyanex 272 for cobalt and nickel extraction. It is efficient for selective cobalt extraction from high Ni/Co ratio solutions. Abstract: Cobalt and nickel are important strategic resources. Solvent extraction is an efficient way to separate and recover cobalt and nickel from spent batteries like ternary LIBs, NiMH and Ni-Cd batteries. In this paper, we introduce an unsymmetrical dialkylphosphinic acid INET-3 – which possesses excellent extraction and separation performance for heavy REEs – to cobalt/nickel separation for the first time. We investigated its extractabilities for cobalt and nickel and did some comparisons with those of MEXTRAL 507P and Cyanex 272. We studied effects of several parameters on cobalt/nickel separation including saponification ratio, Ni/Co ratio, temperature and anions (SO4 2− and Cl − ). We also evaluated its extraction capacity for cobalt via two methods: one is contacting the organic phase continuously with fresh working solutions, and the other is increasing phase ratio A/O. Besides, we explored its selectivity for impurities including copper, zinc, manganese, calcium and magnesium and studied stripping behaviors of cobalt and nickel coordinated with INET-3. The results show INET-3 has stronger extractability for cobalt and nickel than Cyanex 272, while weaker extractability than MEXTRAL 507P. High saponification ratio and temperature favor cobalt/nickel separation, while SO4 2− and Cl − are on the contrary. For systems with Ni/Co ratio ≤81:1, the Co/Ni separation factors all exceeded to 130. The selectivity of INET-3 was in the order Zn 2+ > Cu 2+ > Mn 2+ > Co 2+ > Mg 2+ ≈ Ni 2+ > Ca 2+ . Its extraction capacity for cobalt was less than that of Cyanex 272 at the same initial conditions. The loaded cobalt can be easily stripped by diluted sulfuric acid.